Zinc hyperaccumulation in Thlaspi caerulescens - Mills, Victoria (2010)
The total land available to farm globally is only one quarter of the land available. With the current world population currently rising, standing at over 6.6 billion people in August 2008, a need to produce larger food quantities is an ever increasing pressure to scientists and farmers. The options available to support demands are to produce crops that have higher yields grown on land we currently have available, crops with increased tolerance to abiotic stresses, such as saline toxicity and crops to reclaim land that has been damaged by human use such as heavy metal contaminated land. There are currently over 400 plant species belonging to 45 different families that can tolerate and accumulate excessive amounts of heavy metals, such as nickel, cadmium and zinc. Thlaspi caerulescens a member of the family Brassicaceae (which is therefore closely related to Arabidopsis thaliana), is a well studied model for studying heavy metal accumulation as it accumulates zinc, nickel and sometimes cadmium to high levels without showing signs of toxicity. The primary aim of this research was to identify and confirm potential genes responsible for the hyperaccumulation of zinc, using microarray and qPCR technologies. The second aim was to functionally test any highlighted, potential candidate genes through transgenics, therefore this project aimed to develop a transformation protocol to study potential candidate genes in planta. The microarray successfully identified genes that were differentially expressed in the hyperaccumulator T. caerulescens compared to T. avense, several were confirmed by qPCR. A good candidate gene from this and other studies on Thlaspi caerulescens and Arabidopsis haleri was HMA4 which is a member of the P1B-ATPase family. An RNAi construct was successfully made of the HMA4 gene in an attempt to silence the gene in planta. Attempts were made to transform Thlaspi caerulescens through tissue culture and floral dip methods; however these were unsuccessful due difficulties of T. caerulescens cultivation and transformation. Future strategies would include rapid cycling of plants and heterologous expression of native T. caerulescens genes in Arabidopsis thaliana.